Anaerobic biodegradation of catechol by sediment microorganisms: Interactive roles of N reduction and S cycling. (1st September 2019) - Zheng, Xiong; Zhou, Chen; Liu, Zhuolin; Long, Min; Luo, Yi-Hao; Chen, Tengfei; Ontiveros-Valencia, Aura; Rittmann, Bruce E.
Abstract: Catechol is one of the central intermediates in the aerobic biodegradation of numerous benzene-based aromatic contaminants derived from coal and petroleum sources as a result of unsustainable production processes. In O2 -limiting environments, such as aquifers and sediments, accumulation of dead-end and inhibitory catechol can lead to a complete shutdown of further biodegradation. Thus, O2 -independent catechol biotransformation plays an essential role in biodegrading aromatic contaminants in anoxic zones. In this study, we investigated redox processes and microbial community change during anaerobic catechol biodegradation coupled to nitrate and sulfate reductions by a sediment consortium. Denitrifiers and sulfate-reducing bacteria initially oxidized soluble non-catechol organics present in the sediments as electron donors to drive denitrification and sulfate reduction, respectively. Once the non-catechol organics were depleted, catechol was activated by denitrifiers capable of benzoyl-CoA metabolism. Subsequent ring cleavage and mineralization produced electrons and energy that could be coupled by denitrifiers and sulfate reducers to nitrate and sulfate reduction to N2 and sulfide, respectively. When nitrate and sulfate coexisted, accumulation of sulfide stimulated sulfide oxidizers to growth via sulfide oxidation coupled to nitrate reduction to ammonium and nitrite. The resulting buildup of nitrite triggered abiotic conversion of catechol to a significantly less bioavailable form, probably 1, 2-benzoquinone, that eventually blocked the biological process of catechol mineralization. This study documents the interactions of the several anaerobic microbial groups during catechol biodegradation with multiple endogenous electron acceptors and provides baseline for sustainable in-situ bioremediation of aromatic-contaminated environments. Graphical abstract: Image 1 Highlights: Anaerobic catechol scavenge is crucial for complete aromatic degradation in O2 -limiting zones. Catechol activation was initiated after the majority of non-catechol organics were depleted. Catechol was activated by denitrifiers capable of benzoyl-CoA metabolism. Catechol and other sCOD breakdown produced electrons for denitrification and SO4 2− reduction. NO3 − accumulation during SOB-enabled DNRA abiotically blocked catechol biodegradation.